A pragmatic analysis of politeness strategies in Mulan movie - Ziaul Fitri (English Education Journal, 2022)
Pragmatics deals with language use in the context that relates to the speech acts' meaning. Politeness strategies and politeness principles, as the manifestation of pragmatics, are two determining communication factors of both speaker and hearer. This qualitative study was intended to analyze the politeness strategies used by the main character Mulan and her family. The data were collected using the observation checklist adapted from Brown and Levinson (1987) framework for politeness strategies. The findings showed that all of Brown and Levinson’s strategies were found in Mulan’s and the other characters’ utterances in the movie. The most frequently used strategy was positive politeness, which was found to occur four times in the movie. Bald-on record and negative politeness were the second most used strategies in the movie with three occurrences each. While off-record and don’t do FTA occurred twice and once, respectively. The result of the pragmatic analysis showed that the use of politeness strategies in Mulan movie was influenced and determined by the characters’ cultural background.